METHODOLOGY OF DEVELOPING ACMEOLOGICAL ACCOMPLISHMENT IN FUTURE TEACHERS - Tuychieva Sabina Sherzodovna (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract:  This  article  examines  the  methodology  of  developing  acmeological accomplishment  in  future  teachers.  The  research  highlights  the  importance  of professional  competence,  reflective  thinking,  and  innovative  pedagogical  activity. Special attention is given to the formation of creative individuality and the achievement of  the  highest  levels  of  professional  development.  The  acmeological  approach  is analyzed  as  a  key  factor  in  ensuring  the  effectiveness  of  pedagogical  activity  and continuous self-improvement.